SOME UNIQUENESS RESULTS ON MEROMORPHIC FUNCTIONS SHARING TWO SETS - Abhijit Banerjee, Abhijit; Bhattacharjee, Pranab (Italian Journal of Pure and Applied Mathematics, 2014)
Using the notion of weighted sharing, we prove some uniqueness theorems of meromorphic functions that share two sets. The results in this paper improve and supplement some recent ones of the first author and consequently provide a better answer to the famous question of Gross than that was given previously.